Revision of the demographic and clinical data of patients with ulcerative colitis in Turkey - Hatice Karagoz; Abdulsamet Erden; Hatice Karaman; Ahmet Karaman (Medicinski glasnik, 2017)
Aim: To evaluate the demographic and clinical data of fifty two patients with the diagnosis of ulcerative colitis. Methods: A total of 52 patients diagnosed with ulcerative colitis by clinical, endoscopical and histopathological evaluations were included the study. Demographic data, colon involvement site of the disease and disease severity were examined from the patients' records. The patients were divided into groups according to the Baron grading system. Results: Distribution of patients according to the colon involvement site was: 10 (9.2%) rectal, 16 (30.8%) rectosigmoid, 13 (25%) left sided, 10 (19.2%) extensive colitis and 3 (5.8%) pancolitis. According to colon involvement sites and Baron classification the results were: five (9.6 %), two (3.8%) and three (5.7%) patients with ulcerative proctitis were at grade 1, 2 and 3, respectively. Two (3.8%), six (11.5 %), six (11.5 %) and two (3.8%) patients with rectosigmoid ulcerative colitis were at grade 0, 1, 2 and 3, respectively. Four (7.6 %), five (9.6%) and four (7.6%) patients with left sided ulcerative colitis were at grade 1, 2, and 3, respectively. One (1.9 %), three (5.7%), and six (11.5 %) patients with extensive ulcerative colitis were at grade 1, 2 and 3, respectively. All three (5.7%) patients with pancolitis were at grade 3 (p=0.11) Conclusion: The ratio of pancolitis is found to be lower in our series. There was no statistically significant difference among the genders according to the age, involvement site and the severity of the disease as well as according to the colon involvement sites and grading.
Keywords: disease severity; inflammatory bowel diseases; colonoscopy; classification